PERSIAPAN MUBALIGH DALAM MENGEMAS MATERI TABLIGH - Marhen Marhen (Alfuad: Jurnal Sosial Keagamaan, 2018)
This study aims to find out the preparation of the preacher in packing messages and the impression of the tabligh in Nagari Pakan Rabaa, Koto District Parik Gadang Di Ateh, South Solok Regency, West Sumatra. The method used in this research is field research with a qualitative approach. The source of this research data is the Mubaligh and worshipers of the mosque and mushalla in the Pakan Rabaa kenagarian, and are supported by theories in books that are related to research problems. Data were analyzed by purposife sampling method, that is selecting samples from the population based on certain considerations, data were analyzed descriptively, analysis of data obtained through interviews and other written data would be linked to one another. From the research carried out, it was concluded that in general the preachers in Kenagarian Pakan Rabaa, Koto Subdistrict Parik Gadang in Ateh, Kabupaten Solok Selatan made preparations before going high and could be said to have fulfilled the ideal category. However, there are still deficiencies on some sides, such as the totality of the mubaligh in applying their tablighic material which is still considered minimal by worshipers, so that the impression of a tabligh message that has been built spontaneously becomes faded.